The United States Naval Academy’s Center for Middle East and Islamic Studies - Brannon Wheeler (International Institute of Islamic Thought, 2007)
In August 2005, the Center for Middle East and Islamic Studies was established at the United States Naval Academy in Annapolis, Maryland. This was the result of a multi-year review of the academy’s curriculum as part of far-reaching efforts under Admiral Rodney Rempt, the current superintendent, to provide a more international and interdisciplinary curriculum to the students ...